Voluntary reporting system in anaesthesia: is there a link between undesirable and critical events?. Issue 4 (1st December 2000) - Boëlle, P-Y; Garnerin, P; Clergue, F; Sicard, J-F; Bonnet, F
Abstract : Background —Reporting systems in anaesthesia have generally focused on critical events (including death) to trigger investigations of latent and active errors. The decrease in the rate of these critical events calls for a broader definition of significant anaesthetic events, such as hypotension and bradycardia, to monitor anaesthetic care. The association between merely undesirable events and critical events has not been established and needs to be investigated by voluntary reporting systems. Objectives —To establish whether undesirable anaesthetic events are correlated with critical events in anaesthetic voluntary reporting systems. Methods —As part of a quality improvement project, a systematic reporting system was implemented for monitoring 32 events during elective surgery in our hospital in 1996. The events were classified according to severity (critical/undesirable) and nature (process/outcome) and control charts and logistic regression were used to analyse the data. Results —During a period of 30 months 22% of the 6439 procedures were associated with anaesthetic events, 15% of which were critical and 31% process related. A strong association was found between critical outcome events and critical process events (OR 11.5 (95% confidence interval (CI) 4.4 to 27.8)), undesirable outcome events (OR 4.8 (95% CI 2.0 to 11.8)), and undesirable process events (OR 4.8 (95% CI 1.3 to 13.4)). For other classes of events, risk factors were related to the course of anaesthesia (duration, occurrence of other events) and included factors determined during the pre-anaesthetic visit (risk of haemorrhage, difficult intubation or allergic reaction). Conclusion —Undesirable events are associated with more severe events and with pre-anaesthetic risk factors. The way in which information on significant events can be used is discussed, including better use of preoperative information, reduction in the collection of redundant information, and more structured reporting. ( Quality in Health Care 2000;9 :203–209)